Nematodes can substitute Artemia in a co-feeding regime for pacific white shrimp post-larvae reared in a biofloc nursery system - Sommer, Nils (2024)
This study evaluated nematodes as an alternative to live Artemia when provided in a co-feeding regime to Pacific white shrimp (Penaeus vannamei) post-larvae (PL) reared in a biofloc nursery system. A 20-day experiment employing PL11 was performed for an evaluation of four dietary groups: control [C] (fed exclusively with a dry commercial feed); artificial Artemia [AA] (dry feed composed of extracted and processed Artemia cysts and dry commercial feed); live Artemia and dry commercial feed [LA]; and nematodes and dry commercial feed [N] (Panagrolaimus sp. dry nematodes). The diets were provided twice a day, with the remaining six feed provisions being a commercial dry feed for all experimental groups. A biofloc system was chosen as it offers a potentially sustainable approach to intensive shrimp farming. Alkalinity and pH in the [N] group were significantly higher in the last 5 days of the experiment (p < 0.05), likely causing the significantly lower nitrite levels observed in that same group (p < 0.05). Total and volatile suspended solids were significantly lower in the two live feed groups when compared with [C] and [AA] (p < 0.05). Although PL fed the dry diets exhibited higher growth rates (p < 0.05), the [N] and [LA] groups presented significantly higher final survivals (p < 0.05). No differences were found for survival after a salinity stress test (p ≥ 0.05). These results suggest that nematodes can successfully substitute Artemia in a co-feeding regime for P. vannamei PL reared in biofloc nursery systems.